PENINGKATAN KETERAMPILAN SISWA SD INPRES MATAUE MELALUI PENERAPAN ECOPRINT BERBASIS DEDAUNAN - Farid; iftita Kending (Sambulu Gana : Jurnal Pengabdian Masyarakat, 2025)
This community service activity aims to improve the skills of students at SD Inpres Matawue through the application of leaf-based ecoprint techniques. Ecoprint is an environmentally friendly fabric coloring method that utilizes natural pigments from plants, as well as being an educational medium to instill values ??of environmental concern from an early age. This activity was carried out with a qualitative descriptive approach through three main stages: planning, implementing ecoprint practices, and evaluating student work. The subjects of the activity were grade V students, with data collection techniques in the form of observation, interviews, and documentation. The results of the activity showed an increase in aspects of fine motor skills, creativity, and students' aesthetic sensitivity. In addition, students showed high enthusiasm and gained a fun contextual learning experience. This activity shows that ecoprint can be used as an alternative to skills-based learning that supports character education and a love of nature.